An international, multicentre, double-blind, randomized study (DISSCO): effect of diacerein vs celecoxib on symptoms in knee osteoarthritis. (10th June 2020) - Pelletier, Jean-Pierre; Raynauld, Jean-Pierre; Dorais, Marc; Bessette, Louis; Dokoupilova, Eva; Morin, Frédéric; Pavelka, Karel; Paiement, Patrice; Martel-Pelletier, Johanne; ,
Abstract: Objective: The objective of this study was to investigate whether diacerein has comparable efficacy with celecoxib in pain reduction for treatment in symptomatic knee OA patients. Methods: This randomized double-blind multicentre non-inferiority trial evaluated diacerein vs celecoxib treatment in patients with Kellgren–Lawrence grade 2–3 and pain scoring ≥4 (10-cm VAS). Patients were randomized to 6 months of treatment with diacerein 50 mg ( n = 187) once daily for 1 month and twice daily thereafter, or celecoxib 200 mg ( n = 193) once daily. The primary outcome was the change in WOMAC pain score (0–50 cm) at 6 months, and the secondary outcomes were WOMAC sub-scores, VAS pain score, and the OMERACT–OARSI responder rate. Results: In the per protocol population, the adjusted mean change from baseline in the WOMAC pain score was –11.1 ( 0.9) with diacerein ( n = 140) and –11.8 (0.9) with celecoxib ( n = 148). The intergroup difference was 0.7 (95% CI: −1.8, 3.2; P = 0.597), meeting the non-inferiority margin. Supportive analysis of the intention-to-treat population gave similar results. Other outcomes showed no significant difference between treatment groups. The incidence of treatment-related adverse events was low and balanced between groups, but a greater incidence of diarrhoea occurred with diacerein (10.2% vs 3.7%). Diarrhoea was considered mild-to-moderate in all but one case with complete resolution. Conclusions: Diacerein was non-inferior to celecoxib in reducing knee OA pain and improving physical function. Diacerein also demonstrated a good safety profile. Trial registration: A multicentre study on the effect of DIacerein on Structure and Symptoms vs Celecoxib in Osteoarthritis is a National Institutes of Health (NCT02688400) and European Clinical Trial Database (2015–002933-23) registered phase III (Canada) or IV (Europe) study.